A comparison of four shoulder-specific questionnaires in primary care. Issue 10 (10th September 2004) - Paul, A; Lewis, M; Shadforth, M F; Croft, P R; van der Windt, D A W M; Hay, E M
Abstract : Objectives: To compare the validity, responsiveness to change, and user friendliness of four self completed, shoulder-specific questionnaires in primary care. Methods: A cross sectional assessment of validity and a longitudinal assessment of responsiveness to change of four shoulder questionnaires was carried out: the Dutch Shoulder Disability Questionnaire (SDQ-NL); the United Kingdom Shoulder Disability Questionnaire (SDQ-UK); and two American instruments, the Shoulder Pain and Disability Index (SPADI) and the Shoulder Rating Questionnaire (SRQ). 180 primary care consulters with new shoulder region pain each completed two of the questionnaires, as well as EuroQoL and 10 cm visual analogue scales (VAS) for overall pain and difficulty due to the shoulder problem. Each participant was assessed by a standardised clinical schedule. Postal follow up at 6 weeks included baseline measures and self rated assessment of global change of the shoulder problem (seven point Likert scale). Results: Strongest correlations were found for SDQ-UK with EuroQoL 5 score, and for SPADI and SRQ with shoulder pain and difficulty VAS. All shoulder questionnaires correlated poorly with active movement at the painful shoulder. SPADI and SRQ performed better on ROC analysis than SDQ-NL and SDQ-UK (areas under the curve of 0.87, 0.85, 0.77, and 0.77, respectively). However, SRQ scores changed significantly over time in stable subjects. Conclusions: Cross sectional comparison of the four shoulder questionnaires showed they had similar overall validity and patient acceptability. SPADI and SRQ were most responsive to change. Additionally, SPADI was the quickest to complete and scores did not change significantly in stable subjects.